The Utilisation of Waste Bamboo Shells as A Filler in The ACWC Mixture on Marshall Characteristics - Irwanto, Taurina Jemmy; Setiawan , Aldi; Mukti, M. Hazin (Future Science / FSH-PH Publications, 2022)
Roads as transportation system infrastructure that are routinely used to support human activities every day must have adequate quality. The increase in the number of public and private vehicles results in the use of roads that continue to increase to the potential road damage if they do not have adequate quality. One of the factors of the quality of road infrastructure is the road pavement. This study is to examine the effects of bamboo shell powder as Filler on the ac-WC hot asphalt mixture on the characteristic value of Marshall. In this study we used Marshall Testing. This research was carried out in laboratories, starting from literature studies, material collection, material testing, determination of mixed plan asphalt levels, preparation and manufacture of test objects and Marshall testing. This study found bamboo shells to be one of the mixed materials in the hot asphalt mixture so that it becomes an asset for residents in the future.